Professional education and CTS: a view on the federal institutes - Silva, Sidney Reinaldo da; Fernandes, Rodrigo Rafael (Universidade Estadual de Campinas, 2019)
This text takes an approach to the principles of professional training of the Federal Institutes (FIs) and their correlation with an approach in the field of Science Technology and Society (STS). Its objective was to show how the policies that underpin the institutionality of FIs contribute to think about professional training in the STS perspective, that is, in a socially engaged way. Atfirst,adelineationisconstructedbasedonacriticalpresentationoftheSTSfieldandthetypeofprofessionaltrainingassociatedwithit,inorderto,inasecondmoment,indicatetheethical-politicalbasesofeducationintheFIs,resumingthedocumentonitsconceptionsandguidelinesandthelawofitscreation,Lawnº11.892.ItisshownthattheFIspresentthemselvesasaprivilegedspacefortheSTSformation,andmaybetheoccasionfortheassociationofthiswithaconceptionofprofessionaltrainingofworkers,researchersandcitizenscapableofinterveninginthepublicdecisionprocessesinvolvingsciencetechnology.